Open Sesame! The Magical Words of the World of Meaning of Human Beings: Dialectical Harmony of the Symbolical Forms - Kartal, Ümit (My University, 2023)
Ernst Cassirer was made an original contribution to the philosophy of the twentieth century with his genuine series of the Philosophy of Symbolic Forms. Cassirer evaluates the various moments of culture from an integral perspective. Cassirer’s contribution to the philosophical agenda was reinforced by the works An Essay on Man and The Myth of the State. These latter works, however, go beyond mere repetition and summary of Cassirer’s thought. Particularly, The Myth of the State is important to confront a problem left open by Cassirer’s integral philosophy of culture; the return of myth that consolidates contemporary political thought and action. Cassirer defines culture as the progressive process of human emancipation; analyses the element of culture in dialectical harmony, without reducing one to the other. Although Cassirer presents a systematic philosophical framework, it triggers a series of questions waiting to be resolved within itself. In this study, first, the aspects of Cassirer’s philosophy of culture that give the opportunity to comprehend the various dimensions of the human beings’ world of meaning will be discussed in detail. Then, it will be tried to describe the depth and limit of the original cultural analysis revealed by this systematic approach to update itself in the face of a historical problem.
Keywords: Culture; History; Self-Knowledge; Symbolic Forms; The World of Meaning; Political Myths